Development of vulnerability curves for school buildings damaged by Typhoon Nina - Galisim, Jeo Jenson G.; Tan, Liezl Raissa E. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The Philippines experienced an average of nine land falling typhoons yearly that caused damage to infrastructure amounting to an average annual cost of Php 8 billion from 2010-2015. Economic losses obtained can be mitigated by strengthening and improving the design of these structures, reducing its susceptibility against severe wind. Hence, studies were conducted to determine the performances of existing design of structures to establish vulnerability curves that can further be used in proposing building designs, predicting damage and estimating damage cost. This study focused on developing empirical vulnerability curves for school buildings. Aside from having a more standardized design than residential buildings, school buildings exist in every community where it is not only used for educational purposes but also as evacuation centers during disaster recovery operations. Post-damage assessment of school buildings in areas highly affected by Typhoon Nina was conducted. Together with the damage reports obtained from the DepEd regional office, a total of 422 damage data on school buildings were acquired. The classifications of school building considered in assessment include Marcos, BLSB I, RP-US, DECS and DepEd Standard. Damages were quantified as ratio of damage cost to the total building construction cost, defined as the damage ratio. These were plotted against the corresponding maximum local wind speed retrieved from an opensource wind speed data mapped by Red Cross Netherlands, generating empirical vulnerability curves. The resulting vulnerability curves, without considering the building age, suggest that DepEd standard is the least vulnerable while Marcos type is the most susceptible to severe wind. Fragility curves at 25%, 50% and 75% damage states were also developed by obtaining the probability of distribution at different wind speeds and determining the corresponding probability of exceedance. Fragility curves show that for a Marcos type, it is guaranteed that at windspeeds values of 250, 300 and 350kph, considered components were already damaged by 25%, 50% and 75% respectively.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: School buildings -- Aerodynamics; Buildings -- Natural disaster effects